Continuous and Quantitative Purification of T-Cell Subsets for Cell Therapy Manufacturing Using Magnetic Ratcheting Cytometry. (August 2018) - Murray, Coleman; Pao, Edward; Jann, Andrew; Park, Da Eun; Di Carlo, Dino
T-cell-based immunotherapies represent a growing medical paradigm that has the potential to revolutionize contemporary cancer treatments. However, manufacturing bottlenecks related to the enrichment of therapeutically optimal T-cell subpopulations from leukopak samples impede scale-up and scale-out efforts. This is mainly attributed to the challenges that current cell purification platforms face in balancing the quantitative sorting capacity needed to isolate specific T-cell subsets with the scalability to meet manufacturing throughputs. In this work, we report a continuous-flow, quantitative cell enrichment platform based on a technique known as ratcheting cytometry that can perform complex, multicomponent purification targeting various subpopulations of magnetically labeled T cells directly from apheresis or peripheral blood mononuclear cell (PBMC) samples. The integrated ratcheting cytometry instrument and cartridge demonstrated enrichment of T cells directly from concentrated apheresis samples with a 97% purity and an 85% recovery of magnetically tagged cells. Magnetic sorting of different T-cell subpopulations was also accomplished on chip by multiplexing cell surface targets onto particles with differing magnetic strengths. We believe that ratcheting cytometry's quantitative capacity and throughput scalability represents an excellent technology candidate to alleviate cell therapy manufacturing bottlenecks.